Self writing with and without moderation: feminine academic memorials held (USP - UNICAMP, 2000-2015) - Lima da Silva, Wilton Carlos [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2020)
The academic memorial is an autobiographical account that is structured at the confluence of the bureaucratic requirement and the self-narrative, presenting itself as a privileged manifestation of the memory of individuals who stand out in their professional lifes, reaching higher levels of the academic career. In this article, we sought, from thirteen academic memorials of professors approved in tenure contests in the Departments of History and Anthropology at USP and UNICAMP between 2000 and 2015, to discuss some issues regarding the female condition, in particular, about class conditions, race and gender. The documentary scope also offers elements for problematizing the processes of building self-writing, having ego-history and self-ethnography as references, based on markers about family origins; inheritance, work and legacy, professional activities and corporality.
Keywords: Academic Memorial; Memory; Ego-History; Self-Ethnography